Off‐tenofovir hepatitis flares in HBeAg‐negative patients occur earlier, more frequent and severe than those off‐entecavir therapies. (6th January 2022) - Liu, Yen‐Chun; Jeng, Wen‐Juei; Peng, Chien‐Wei; Chien, Rong‐Nan; Liaw, Yun‐Fan
Abstract: Background & Aims: Clinical relapse occurs much earlier and more frequently in hepatitis B e antigen (HBeAg)‐negative chronic hepatitis B (CHB) patients after stopping tenofovir (TDF) therapy than those off‐entecavir (ETV). Clinical relapse may subside or progress to hepatitis flare which poses a safety concern. This study compared the incidence, timing and severity of hepatitis flares after stopping TDF and ETV. Methods: HBeAg‐negative CHB patients who had stopped ETV or TDF were included in the study. Off‐therapy hepatitis flare patterns were compared between off‐ETV and off‐TDF patients before and after propensity score matching (PSM). Results: The off‐therapy hepatitis flares occurred more frequently (2‐year: 58% vs 38%, P  < .001) and much earlier (12 vs. 38 weeks, P  < .001) in TDF group, with higher alanine aminotransferase (ALT) levels (after PSM: 536 vs. 419 U/L, P  = .020) and two times rate of hepatic decompensation (4.0% vs. 2.1%, P  = .322). The cirrhotic status [aHR: 20.531 (2.645‐159.365), P  = .004] and off‐TDF [aHR: 5.530 (1.728‐17.694), P  = .004] were two independent predictors for hepatic decompensation. Conclusions: Hepatitis flare occurred more frequently, earlier, and more severe in off‐TDF than off‐ETV patients. More stringent off‐therapy monitoring within 6 months off‐TDF is mandatory whereas more attention is needed after 6 months off‐ETV.